2018
DOI: 10.3390/app8101819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Illumination Polarization and Target Structure on Measurement Sensitivity of Through-Focus Scanning Optical Microscopy

Abstract: Unlike the optical information taken from a single in-focus image of general optical microscopy, through-focus scanning optical microscopy (TSOM) involves scanning a target through the focus and capturing of a series of images. These images can be used to conduct three-dimensional inspection and metrology with nanometer-scale lateral and vertical sensitivity. The sensitivity of TSOM strongly depends on many mechanical and optical factors. In this study, how illumination polarization and target structure affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Subsequently, the TSOM image can be extracted from these defocusing images and further processed according to the methods by Attota & Kang () and Qu et al . (). The differential TSOM (DTSOM) image is obtained by directly subtracting one TSOM image from the other.…”
Section: Methodsmentioning
confidence: 97%
“…Subsequently, the TSOM image can be extracted from these defocusing images and further processed according to the methods by Attota & Kang () and Qu et al . (). The differential TSOM (DTSOM) image is obtained by directly subtracting one TSOM image from the other.…”
Section: Methodsmentioning
confidence: 97%
“…The first paper on 3D surface profile measurement is introduced by Qu and his colleagues at Beihang University on the measurement sensitivity of through-focus scanning optical microscopy (TSOM), which involves scanning a target through the focus and capturing of a series of images [1]. It was found that for enhanced sensitivity, illumination polarization should be perpendicular to the target texture.…”
Section: Surface Profile and Form Error Measurementsmentioning
confidence: 99%